Technologies, knowledge and capital : towards a political ecology of the Hake Trawl Fishery Walvis Bay, Namibia - Draper, Kelsey (Social Anthropology, 2014)
Around the world, the implementation of effective fisheries management has been met with a variety of challenges. The incorporation of fisher's local ecological knowledge (FK) into the management paradigm is an important step in understanding perceptions and responses to the changing environment, and emerges as an indispensable component in the dialogue between trans-disciplinary coastal ecology studies. This dissertation seeks to contribute to the integration of these knowledges, and emphasises the involvement of fishers, communities, and research in informing policy.